(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Combinatorial chemistry is a new methodology by which we can simultaneously synthesize a number of possible compounds that could produce simultaneously a very large number of compounds, called libraries. Combinatorial chemistry involves the rapid synthesis or the computer simulation of a large number of different but often structurally related molecules or materials. Combinatorial chemistry is especially common in CADD (Computer aided drug design) and can be done online with web based software, such as Molinspiration.In the past, chemists have traditionally made one compound at a time.